2018
DOI: 10.1111/gfs.12372
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sainfoin (Onobrychis viciifolia Scop.) germplasm for agro‐morphological traits and nutritive value

Abstract: Sainfoin (Onobrychis viciifolia Scop.) is a bloat‐free, perennial forage legume adapted to the northern temperate regions of the world. This study was carried out to evaluate phenotypic variation and nutritive value of 38 sainfoin accessions from 21 different countries. A field trial was established in 2014 using a randomized complete block design with four replications near Saskatoon, Canada, with data collected in 2015 and 2016. Analysis of variance revealed significant (p < 0.05) differences among sainfoin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
3
18
1
Order By: Relevance
“…This study found a high degree of diversity for agromorphological traits among the cicer milkvetch populations except for leaf number per stem at the first harvest. The high interpopulation variability found in our study was also seen in the agronomic and morphological traits of other perennial species, including alfalfa (Jenczewski et al 1998;Li et al 2009), sainfoin (Delgado et al 2008;Jafari et al 2014;Bhattarai et al 2018), and crested wheatgrass (Agropyron cristatum (L.) Gaertn.) (Tandoh et al 2019).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This study found a high degree of diversity for agromorphological traits among the cicer milkvetch populations except for leaf number per stem at the first harvest. The high interpopulation variability found in our study was also seen in the agronomic and morphological traits of other perennial species, including alfalfa (Jenczewski et al 1998;Li et al 2009), sainfoin (Delgado et al 2008;Jafari et al 2014;Bhattarai et al 2018), and crested wheatgrass (Agropyron cristatum (L.) Gaertn.) (Tandoh et al 2019).…”
Section: Discussionsupporting
confidence: 69%
“…The diversity within germplasm collections of alfalfa (Jenczewski et al 1998;Li et al 2009) and sainfoin (Onobychis viciifolia Scop.) (Delgado et al 2008;Jafari et al 2014;Bhattarai et al 2018) has been studied extensively. These studies have shown that plant height (Li et al 2009;Bhattarai et al 2018), stem number per plant (Jafari et al 2014;Bhattarai et al 2018), and the presence of rhizomes (Jenczewski et al 1998) can differentiate populations within germplasm collections for these two species.…”
Section: Introductionmentioning
confidence: 99%
“…It does not cause bloat in grazing animals, and can provide palatable, high-quality forage (Bhattarai, Coulman & Biligetu, 2016; Frame, 2005). Sainfoin contains high levels of condensed tannins that sainfoin has shown to reduce parasites in the ruminant digestive tract and provide environmental benefits by reducing methane emissions from ruminant animals (Malisch et al, 2015; Sottie et al, 2014; Bhattarai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bhattarai et al studied 38 Onobrychis viciaefolia Scop. materials from 21 different countries and concluded that the dry matter yield of these materials ranged from 74 to 239 g/plant (Bhattarai et al 2018). This suggests that plant genotype and environment have an effect on yield and breeding efforts to improve this plant will be helpful for the future growth of the forage industry.…”
Section: Introductionmentioning
confidence: 99%